ANALISIS PENDAPATAN USAHA ABON IKAN TUNA ( STUDI KASUS PADA USAHA KELOMPOK WANITA NELAYAN “ FATIMAH AZ-ZAHRAH ” DI KELURAHAN PATTINGALLOANG KECAMATAN UJUNG TANAH KOTA MAKASSAR ) - Usman Usman; Syafiuddin Syafiuddin; St. Aisyah R. (OCTOPUS : JURNAL ILMU PERIKANAN, 2016)
This study aims to determine the income of fish tuna business by the Fishermen Women Group "Fatimah Az-Zahrah" in Kelurahan Pattingalloang Ujung Tanah Subdistrict Makassar City. The type of research used is a case study on the business of the Fishermen Group "Fatimah Az-Zahrah" in Kelurahan Pattingalloang Kecamatan Ujung Tanah Makassar. The research used purposive sampling technique in determining the informant. This research was conducted on May to July 2014 which is in Kelurahan Pattingalloang Subdistrict Ujung Tanah Makassar City. The research location was chosen purposely because the location of this research is one of tuna processing industry centres in Makassar. The results of this study indicate the existence of tuna development efforts by the Fishermen Group "Fatimah Az-Zahrah" in Pattingalloang Urban District Ujung Tanah Makassar City Rp 254.284.600/year and monthly income abon tuna fish an average of Rp 21,190. 383.3.